High-Performance Ultrathin Molecular Rectifying Diodes Based on Organic/Inorganic Interface Engineering - Batista, Carlos Vinicius Santos [UNESP]; Merces, Leandro; Costa, Carlos Alberto Rodrigues; de Camargo, Davi Henrique Starnini; Bufon, Carlos César Bof [UNESP] (Wiley, 2022)
The bottom-up engineering of organic/inorganic hybrids is a crucial step toward advanced nanomaterial technologies. Understanding the energy level alignment at hybrid interfaces provides a valuable comprehension of the systems′ electronic properties – which are decisive for well-designed device applications. Here, active interfaces of ultrathin (≈10 nm) molecular rectifying diodes that are capable of achieving a 4-order-magnitude rectification ratio along with 10 MHz cutoff frequency, both in a single nanodevice, are engineered. Atomic force microscopy and Kelvin-Probe analysis are employed to investigate the surface potential of the hybrid devices′ organic/inorganic interfaces, which comprise a metal (M) electrode in contact with a few-nanometer-thick copper phthalocyanine (CuPc) film. Thereby a nanometer-resolved quantification of the CuPc film work functions as well as the M/CuPc diode's space-charge densities are delivered. By recognizing that the molecular rectifying diode is a functional building block for nanoscale electronics, the findings address crucial advances to the design of high-performance molecular rectifiers based on organic/inorganic interface engineering.